Plan sceneries strategic decision making in Ibb university - Al-Ofiry, Nabeel Ahmed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to plan sceneries of strategic decisions making in Ibb University. Both qualitative and quantitative methodologies were used in this study. A deep interview, a questionnaire, and focus groups were administered to a purposive sample to collect the data. Then, Alpha Cronbach, means, and standard deviations were calculated. The study revealed a number of findings; most notably: the situation of making strategic decisions appeared spontaneous and random, attention was paid to peripheral issues, risk appearance, manoeuvre weaknesses, conflicts appearance, and absence of dialogue culture; the experts were looking forward to override the general interest of the university in the future, build real partnerships and alliances, invest resources better, and reinforce a democratic participation; the most importantly higher effective factors in making strategic decisions were pressures of wages and salaries, and changing needs and requirements of labour market; while the most importantly average effective factors were pressures of local authority officials, pressures of vested-interest people; and the most importantly lower effective factors were pressures of habits and traditions of society, and pressures of partnership with national and international institutions. Finally, three sceneries of strategic decisions making were for mulated in the absence of a certain environment: i) Shock Scenario; ii) Crisis Scenario; and iii) Distortion Scenario.
Keywords: External and Internal Factors; Effect; Uncertainty; Events; Risks; Reactions